Sonographic Nomogram of the Leptomeninges (Pia-Glial Plate) and Its Usefulness for Evaluating Bacterial Meningitis in Infants - Jéquier, Sigrid; Jéquier, Jean-Claude (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: To our knowledge, the upper limits of the thickness of normal meninges on neurosonograms are not known. We therefore established a nomogram for sonographic measurements of the leptomeninges (pia-glial plate) and assessed its usefulness in neurosonographic examinations of children with bacterial meningitis.METHODS: The pia mater–cortical glia limitans complex on the surface of the brain and in the sulcus of a frontal gyrus was measured on neurosonograms in 100 infants without meningeal disease in order to establish a nomogram of the thickness of this pia-glial plate, referred to as the leptomeninx. Effects of prematurity, age, sex, and single-layer (surface) versus double-layer (sulcus) measurements were analyzed. Meningeal thicknesses derived from a retrospective analysis of the neurosonograms of 33 patients with purulent meningitis and a prospective study of 22 patients with bacterial meningitis were compared with the nomograms. Clinical outcomes of children with meningeal thickening were compared with those of affected children with normal meninges.RESULTS: The distribution of sulci measurements was significantly asymmetrical around the mean. Statistical data showed no influence of prematurity and sex, but showed surface measurements to be more consistent than sulcal measurements. Older chronological age was related to slightly larger sulci, but did not influence the surface measurements. In children with bacterial meningitis, the surface meninges were less frequently thickened than were the sulci. Sulcal enlargement occurred often in combination with echogenic deposits in the subarachnoid space.CONCLUSION: Leptomeninges are best measured on the surface of a gyrus rather than in a sulcus, as the normal thickness of the sulci shows much more variability. Clinical outcome of bacterial meningitis cannot be predicted by presence or absence of meningeal thickening as the only sonographic abnormality.